THERMODYNAMIC MODEL OF NATURAL BRINES ACCOUNTING FOR THE PRESENCE OF TRACE COMPONENTS. I. SYSTEM NA+, K+, MG 2+, CA2+, SR2+, BA2+ ∥ CL-, SO42- - H2O - Charykova M.V.; Charykov N.A. (My University, 2004)
This paper presents the results of calculations of binary and ternary parameters of the Pitzer equation and the thermodynamic potentials of solid phases crystallizing in the water-salt systems that model chloride brines taking into account the presence of strontium and barium ions. Phase solubility diagrams were calculated for the respective three- and four-component systems containing sodium, potassium, magnesium, calcium, strontium, and barium chlorides within a temperature interval of 0-40degreesC. The results of calculations are consistent with the limited experimental data on solubility and can be used for modeling the crystallization of salts in the course of seawater and brine concentration, subsequent burial, and interaction with the host rocks.